2018
DOI: 10.1038/s41598-018-35014-1
|View full text |Cite|
|
Sign up to set email alerts
|

The beneficial effects of Lactobacillus reuteri ADR-1 or ADR-3 consumption on type 2 diabetes mellitus: a randomized, double-blinded, placebo-controlled trial

Abstract: Probiotics have been reported to ameliorate symptoms of type 2 diabetes mellitus (T2DM) in animal models and human studies. We previously demonstrated that oral administration of Lactobacillus reuteri ADR-3 reduced insulin resistance in high-fructose-fed (HFD) rats. In the present study, we first identified another L. reuteri strain, ADR-1, which displayed anti-diabetes activity that reduced the levels of serum HbA1c and cholesterol and that increased antioxidant proteins in HFD rats. We further performed a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 37 publications
(36 reference statements)
3
120
0
1
Order By: Relevance
“…These results suggested that fragmented CP1563 reduced abdominal fat area, body weight, and BMI in pre-obese subjects. Several human clinical trials showed an anti-obesity effect of the intake of paraprobiotics [25][26][27]. The anti-obesity effect of fragmented CP1563 in this study supported the results of a previous study, which showed the anti-obesity effect of fragmented CP1563 [30].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results suggested that fragmented CP1563 reduced abdominal fat area, body weight, and BMI in pre-obese subjects. Several human clinical trials showed an anti-obesity effect of the intake of paraprobiotics [25][26][27]. The anti-obesity effect of fragmented CP1563 in this study supported the results of a previous study, which showed the anti-obesity effect of fragmented CP1563 [30].…”
Section: Discussionsupporting
confidence: 90%
“…Few findings have focused on the effects of the oral intake of paraprobiotics on the gut microbial community in obesity prevention [26,27]. In addition, there is no evidence about the effects of fragmented CP1563 on the gut microbial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e antioxidant and inflammatory status of the patients were not affected by the probiotic supplementation. Both the strains of L. reuteri exhibited health-promoting property with unique in uences on fecal microbiota and other DM-associated parameters [23].…”
Section: Probiotic Supplementmentioning
confidence: 99%
“…Another important approach with associated probiotics (Bifidobacterium, Lactobacillus, and S. thermophilus) for treatment of overweight patients has shown an improvement in lipid profile, as well as insulin sensitivity [82]. Besides, recently Hsieh e collaborators [83] demonstrated that administration of live Lactobacillus reuteri ADR-1 and killed Lactobacillus reuteri ADR-3 strain ameliorated type 2 diabetes mellitus in a clinical trial. The results indicated that the consumption of ADR-1 displayed a reduction effect on serum glycated hemoglobin (HbA1c), triglyceride, and cholesterol levels.…”
Section: Metabolic Syndromementioning
confidence: 99%